TUMPANGSARI TANAMAAN PORANG (Amorphophallus muelleri Blume) DENGAN POHON KETIMUNAN (Gyrinops versteegii) DI HKM DESA PUSUK LESTARI, KABUPATEN LOMBOK BARAT - Tri Mulyaningsih; Aida Muspiah; Ernin Hidayati; Faturrahman Faturrahman; Wiwin Hidayat (Universitas Mataram, 2022)
The porang plant (A. muelleri) can produce tubers containing up to 54% glucomannan (which is beneficial for health and industrial materials. This plant can grow well under stands, so it can be intercropped with any tree, including gaharu trees which are conserved ex situ). at HKM Pusuk Lestari, West Lombok. The purpose of this service activity is to provide knowledge about the intercropping cultivation of porang plants with G. versteegii trees planted one year ago for ex-situ conservation in the HKm area of ​​Pusuk Lastari Village, Batu Layar, West Lombok, and provide training as well as the practice of planting porang seedlings in the HKm area with an agroforestry system, to increase income and welfare for HKm stakeholders in Pusuk Lestari Village.The result of this service activity is that training activities have been carried out on porang cultivation using the method of intercropping with G. versteegii trees, starting from selecting quality seeds, distributor search r sales and ordering of porang seeds to, handling of seedlings before planting. Meanwhile, the practice of preparing for planting, such as weeding the land, loosening the soil, making soil rolls, making spacing, and planting porang seedlings were carried out in intercropping with the gaharu tree of the type G. versteegii in the Pusuk Lestari HKM area, West Lombok.